2019
DOI: 10.48550/arxiv.1905.06933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamically Fused Graph Network for Multi-hop Reasoning

Abstract: Text-based question answering (TBQA) has been studied extensively in recent years. Most existing approaches focus on finding the answer to a question within a single paragraph. However, many difficult questions require multiple supporting evidence from scattered text across two or more documents. In this paper, we propose the Dynamically Fused Graph Network (DFGN), a novel method to answer those questions requiring multiple scattered evidence and reasoning over them. Inspired by human's step-by-step reasoning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Guessing has been found unduly successful for the widely used SQuAD QA dataset [9,34]. The complex QA benchmark HotPotQA [48] was supposed to test multi-step reasoning. However, Min et al [28] found that top-scoring QA systems as well as humans could guess the answer without such reasoning for a large fraction of queries.…”
Section: Introductionmentioning
confidence: 99%
“…Guessing has been found unduly successful for the widely used SQuAD QA dataset [9,34]. The complex QA benchmark HotPotQA [48] was supposed to test multi-step reasoning. However, Min et al [28] found that top-scoring QA systems as well as humans could guess the answer without such reasoning for a large fraction of queries.…”
Section: Introductionmentioning
confidence: 99%
“…The graph connects documents that mention the same named entities. To improve scalability, the Dynamically Fused Graph Network (DFGN) (Xiao et al, 2019) adopts a dynamic construction of the graph, starting from the entities in the question and gradually selecting the supporting facts. Similarly, Ding et al (2019) implement a dynamic graph exploration inspired by the dual-process theory (Evans, 2003;Sloman, 1996;Evans, 1984).…”
Section: Hybrid Modelsmentioning
confidence: 99%
“…Answer-aware GCN First we calculate an answer-aware sub-graph, where irrelevant entities are masked out, only those entity nodes related to answer are allowed to disseminate information. Similar to Xiao et al (2019), a soft mask…”
Section: Entity Graph Constructionmentioning
confidence: 99%
“…In addition to the cross-entropy loss, we also introduce Breadth-First Search (BFS) Loss (Xiao et al, 2019) which is a weakly supervised loss to further assist the training procedure. Given the answer entities, we conduct the BFS over the adjacent matrices of the entity graph we build to obtain heuristic masks as a weak supervision signal.…”
Section: Breadth-first Search Lossmentioning
confidence: 99%
See 1 more Smart Citation